Menjaga Kedaulatan Laut Natuna: Diplomasi Pertahanan Indonesia dalam Menghadapi Tekanan Tiongkok - Sandrina Dewi; Wira Atman (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
The North Natuna Sea is an area of strategic importance to Indonesia, both in terms of national security and economy. Legally, this area is part of Indonesia’s Exclusive Zone (EEZ), but China’s unilateral claim to most of this area through the nine-dash line has created tension in the region. Indonesia faces a major challenge to safeguard the sovereignity of this region by using various strategies, one of which is defense diplomacy. This article aims to explore how Indonesia utilizes defense diplomacy in maintaining stability in the Natuna Sea, as well as to analyze the challenges faced and the effectiveness of this approach. The results show that Indonesia’s defense diplomacy can maintain stability, but is still plagued by a number of challenges, including limited resources and the influence of major powers such as China.